Universal Design for Learning (UDL) in simulation-based health professions education - Andrea J. Doyle; Michelle O’Toole; Dara Cassidy; Claire M Condron (Advances in Simulation)
Abstract Background Ensuring equitable access to education is a fundamental goal in health professions training, particularly in simulation-based learning, where realistic clinical scenarios prepare learners for real-world practice. Universal Design for Learning (UDL) offers a robust framework for creating instructional strategies, materials, and environments that are accessible and effective for all learners. Main body In this article, we provide practical guidance and actionable strategies for incorporating UDL principles into simulation-based activities. Engaging in simulation-based education requires a leap of faith and a willingness to embrace vulnerability, as learners must immerse themselves in authentic scenarios. By integrating UDL principles, educators can create a supportive environment that reduces barriers, fosters psychological safety, and ensures that all participants feel empowered to take these risks and fully engage in the learning process. This framework supports opportunities for every learner to partake in meaningful and challenging experiential learning, ultimately preparing them for successful clinical practice. Conclusion From scenario design to debriefing techniques, this article offers insights and recommendations grounded in evidence-based practices, thereby empowering educators to optimize the effectiveness and accessibility of their simulation programs. By embracing UDL principles, educators in health professions education can create simulation experiences that cater to the diverse needs of learners, ensuring that all participants have the opportunity to thrive and succeed in their learning journeys.